2023
DOI: 10.2174/1567202620666230228100653
|View full text |Cite
|
Sign up to set email alerts
|

DL-3-n-butylphthalide Attenuates Cerebral Ischemia-Reperfusion Injury by Inhibiting Mitochondrial Omi/HtrA2-Mediated Apoptosis

Abstract: Background: Ischemic stroke is a major cause of death and disability worldwide and results from inadequate cerebrovascular blood supply; mitochondrial dysfunction plays an essential role in its pathogenesis. DL-3-n-butylphthalide (NBP) is an effective medicine for ischemic stroke that reduces cell apoptosis and improves long-term prognosis. Objective: Whether and how NBP regulates mitochondria-associated apoptosis in cerebral ischemia-reperfusion injury remains unclear. Methods: Male Sprague Dawley rats we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Yan et al [33] found NBP significantly reduced cerebral infarction size, cell apoptosis, BBB damage, and brain edema in mice as a neuroprotective role with I/R injury of MCA occlusion (MCAO) preconditioned. Many researchers have investigated the pathways involved in the neuroprotective effects of NBP.…”
Section: Promising Neuroprotectants and Neuroprotective Therapy In Ai...mentioning
confidence: 99%
“…Yan et al [33] found NBP significantly reduced cerebral infarction size, cell apoptosis, BBB damage, and brain edema in mice as a neuroprotective role with I/R injury of MCA occlusion (MCAO) preconditioned. Many researchers have investigated the pathways involved in the neuroprotective effects of NBP.…”
Section: Promising Neuroprotectants and Neuroprotective Therapy In Ai...mentioning
confidence: 99%